Elastic, Electrical and Thermal Properties of Tellurite Glass Systems - Mohamed Kamari, Halimah (2007)
Three series of tellurite glass were synthesized by melt quenching technique. The binary tellurite was (TeO2)x (B2O3)1-x with x = 60, 63, 65, 70,73, 75, 78, 80 mol%, the ternary tellurite [(TeO2)x (B2O3)1-x]1-y [Ag2O]y consists of three series that is x = 60, 65 and 70 mol% with y = 10, 15, 20, 25 and 30 mol% and quaternary tellurite glass {[(TeO2)x (B2O3)1-x]1-y [Ag2O]y}1-z AgIz with z = 5, 8, 10, 13, 15 mol%. The experimental investigation was divided into two categories. The minor experimental work, which provides supportive evidence to elastic and electrical properties, consists of work on x-ray diffraction, thermal expansion coefficient and optical absorption spectra. The main experiments consist of work on ultrasonic and electrical measurements. The electrical measurements consist of dielectric and ac conductivity properties were measured at low frequencies from 10-2 to 106 Hz while ultrasonic properties were determined with MATEC 8000 at 5MHz resonating frequency and at room temperature. The amorphous structures of the glass samples were evident by the XRD spectrum. Thermal expansion measurement showed that thermal expansion coefficient was composition dependence. The optical absorption spectra of these glasses were measured, the Urbach rule has been applied to evaluate the fundamental absorption edges for all the glasses from the obtained spectrum. The optical band gaps were calculated from the absorption edge and it was found that the optical band gap energy, Eopt depended on the glass composition. The optical band gaps energy showed a decreasing pattern with composition for binary and ternary tellurite glass however it behaves otherwise for quaternary tellurite glasses. Elastic moduli were found dependent on compositions; for binary tellurite system the elastic moduli increased with the increase of TeO2 and for ternary and the quaternary system elastic moduli decreased with Ag2O and AgI respectively. The increase of elastic moduli for binary system was due to the mix former effect and the decreased elastic moduli for ternary was due to Ag2O breaking the bonds of the borotellurite glass system while AgI iodide caused network expansion of the glass structure and weakened the glass structure of this quaternary tellurite system. The Debye temperature and mirohardness had the same trend as the elastic moduli but the Poisson’s ratio always the inverse of the elastic moduli. The results of dielectric response measurements and the results of the equivalent circuit analysis show that electrode polarization at low frequency, orientation polarization at intermediate frequency and polarization of defect glass structure at high frequency are the most probable process responsible for the observed dielectric behaviour of the studied glass samples. The dependence of the alternating current conductivity with frequency at various fixed temperature revealed three distinguishable regions; high frequency dispersion, low frequency dispersion and electrode polarization. The electrical conductivity of tellurite based glass was found to obey the exponential double power law.